Perceived severity of forward versus backward balance disturbances during walking in young and older adults - Shreya Jain; Nicolas Schweighofer; James M. Finley (PLoS ONE, 2025)
Falls, which often result from trips or slips, pose a major health concern, particularly among older adults. Experiencing falls or near-falls from balance disturbances can shape subsequent gait-related decisions, as individuals may avoid situations they perceive as risky or dangerous. Here, we explore whether perceptions of the severity of a gait disturbance are sensitive to the direction of the resulting loss of balance – forward or backward – and whether these perceptions change with age. Twenty young and twenty older adults walked on a split-belt treadmill while performing a two-alternative forced-choice task, where they indicated their preference between a forward-falling and a backward-falling treadmill perturbation. We varied the perturbation magnitudes using an adaptive staircase algorithm to obtain multiple forward-backward equivalence points, which reflect the points at which a forward and a backward perturbation are perceived as being equally severe. Using a mixed-effects linear model, we estimated the slope of this relationship between forward and backward treadmill perturbations, which quantified the direction and strength of the sensitivity to perturbation type. To assess reliability, we repeated the procedure on a second day. Additionally, we investigated two potential reasons underlying any observed sensitivity – 1) emotional responses measured by state anxiety, and 2) physical responses measured by peak center of mass velocity. We found that both young and older adults perceived backward-falling perturbations to be more severe than forward-falling ones, with no group difference in sensitivity. This sensitivity was moderately reliable across two days of testing, though most participants were less sensitive to perturbation direction on the second day. Neither state anxiety responses nor peak center of mass (CoM) velocity explained the directional sensitivity, though deviations in peak CoM velocity from unperturbed walking were higher during backward-falling than forward-falling perturbations for both age groups. These results suggest that the perceived severity of a gait disturbance is not determined solely by its magnitude, but also by its direction, thereby making direction an important component of gait-related decisions. Integrating a measure of relative perception of types of gait disturbances with the ability to recover from them may provide a more comprehensive assessment of fall risk and inform personalized training interventions tailored to individual perceptions and preferences.